Science and technology in world history : an introduction - McClellan, James E., III (James Edward), 1946- (Johns Hopkins University Press, 2015)
Facts and figures have been thoroughly updated and the work includes a comprehensive Guide to Resources, incorporating the major published literature along with a vetted list of websites and Internet resources for students and lay readers.